2022
DOI: 10.3758/s13423-021-02052-2
|View full text |Cite
|
Sign up to set email alerts
|

The role of attention control in complex real-world tasks

Abstract: Working memory capacity is an important psychological construct, and many real-world phenomena are strongly associated with individual differences in working memory functioning. Although working memory and attention are intertwined, several studies have recently shown that individual differences in the general ability to control attention is more strongly predictive of human behavior than working memory capacity. In this review, we argue that researchers would therefore generally be better suited to studying t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
27
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(36 citation statements)
references
References 552 publications
3
27
0
Order By: Relevance
“…Most importantly, when attention control is measured more robustly, it accounts for virtually all the variance in the relationship between working memory capacity and fluid intelligence. This finding is congruent with other research supporting the theoretical position that attention control, and not working memory capacity, is the primary driver of higher-order cognitive behavior (see Draheim et al, 2022). Researchers who continue to use traditional and flawed tasks such as…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…Most importantly, when attention control is measured more robustly, it accounts for virtually all the variance in the relationship between working memory capacity and fluid intelligence. This finding is congruent with other research supporting the theoretical position that attention control, and not working memory capacity, is the primary driver of higher-order cognitive behavior (see Draheim et al, 2022). Researchers who continue to use traditional and flawed tasks such as…”
Section: Discussionsupporting
confidence: 89%
“…Another key finding from Draheim et al (2021) was that attention control fully accounted for the relationship between working memory capacity and fluid intelligence at the latent level, supporting our theoretical position that the ability to control one's attention is the causal basis of the typically strong relationship between working memory capacity and various other higherorder cognitive behaviors (see Burgoyne & Engle, 2020;Burgoyne et al, 2022;Draheim et al, 2022;Shipstead et al, 2016;Tsukahara et al, 2020; also see Conway et al, 2021 andRueda, 2018). In other words, we argue that the ability to control attention is a more important and fundamental driver of higher-order cognition than memory-specific mechanisms such as holding information in primary memory.…”
Section: The Toolbox Approach To Measuring Attention Controlmentioning
confidence: 59%
See 1 more Smart Citation
“…Working memory capacity and attentional control may be additional important individual differences impacting HAT performance. Previous research has found that individuals with a stronger working memory capacity and those with higher attentional control performed better in human-automation interaction in general, but this has not been explored in HATs (Draheim et al, 2021). Further, researchers have found that, due to these cognitive advantages, individuals were better able to detect automation failures, enabling them to step in and complete the task manually (Rovira et al, 2017).…”
Section: Trust In Human-autonomous Teamsmentioning
confidence: 97%
“…Among the three key executive functions, memory updating and inhibitory control, as measured respectively by the running memory span task [ 75 ] and the N-back task [ 76 ], have garnered increasing attention in SLA (e.g., [ 77 ]) and task-based language-teaching research [ 18 , 28 , 78 ]. Similarly, the well-articulated attentional control paradigm by Engle and colleagues [ 79 , 80 ] has been cited widely in the language sciences (cf. [ 81 ]) and interpreting models [ 82 ].…”
Section: Cognitive Wm Models and Measures In Language And Bilingualis...mentioning
confidence: 99%